2020
DOI: 10.2147/ijn.s262582
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Cytotoxic Effect of Cholesterol End-Capped Poly(<em>N</em>-Isopropylacrylamide)s on Selected Normal and Neoplastic Cells</p>

Abstract: Purpose: Efficient intracellular delivery of a therapeutic compound is an important feature of smart drug delivery systems (SDDS). Modification of a carrier structure with a cellpenetrating ligand, ie, cholesterol moiety, is a strategy to improve cellular uptake. Cholesterol end-capped poly(N-isopropylacrylamide)s offer a promising foundation for the design of efficient thermoresponsive drug delivery systems. Methods: A series of cholesterol end-capped poly(N-isopropylacrylamide)s (PNIPAAm) with number-average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…However, it can be supposed that this effect is related to several factors, such as zeta potential value, differences in hydrodynamic diameter, effects related to the presence/absence of the PNIPAAm/PNVCL layer, the number and availability of cholesteryl moieties present at the surface of the particles. It is in line with our previous studies, which showed that homopolymers bearing a cholesteryl moiety can disrupt plasma membranes and cause leakage of lactate dehydrogenase (LDH) from treated neoplastic cells [ 11 ]. It should be emphasized that, based on our results ( Figure S6 ) and previously published studies, the viability of breast cancer cells after treatment with DOX at the concentration of 0.5 µM caused only a slight reduction of viability (10–15%) compared to untreated cells [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, it can be supposed that this effect is related to several factors, such as zeta potential value, differences in hydrodynamic diameter, effects related to the presence/absence of the PNIPAAm/PNVCL layer, the number and availability of cholesteryl moieties present at the surface of the particles. It is in line with our previous studies, which showed that homopolymers bearing a cholesteryl moiety can disrupt plasma membranes and cause leakage of lactate dehydrogenase (LDH) from treated neoplastic cells [ 11 ]. It should be emphasized that, based on our results ( Figure S6 ) and previously published studies, the viability of breast cancer cells after treatment with DOX at the concentration of 0.5 µM caused only a slight reduction of viability (10–15%) compared to untreated cells [ 35 ].…”
Section: Discussionsupporting
confidence: 91%
“…N -isopropylacrylamide (NIPAAm, 99 %, Acros Organics, Geel, Belgium) was recrystallized from toluene–hexane (60:40, v/v ) prior to use. Potassium O -ethyl carbonodithioate (KSCSOEt) was synthesized according to the well-known procedure [ 11 ]. All organic solvents were purchased from Avantor Performance Materials Poland S.A. (Gliwice, Poland) and were distilled before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches result in polymers with one cholesteryl moiety. In the context of drug delivery, recent studies [91] show that even with a relatively long polymer ballast, it is possible to take advantage of the properties of cholesterol present at the polymer chain end. In such systems, cholesterol plays primarily a guiding role, but it can also integrate into the biological membrane, which may allow releasing drug molecules in the immediate vicinity or even inside a pathological cell.…”
Section: Polymers Containing Cholesterol In the Main Chainmentioning
confidence: 99%
“…However, at the same time, they allow for further copolymerization or appropriate modification, e.g., to the thiol group [98], which opens up a variety of possibilities from the Michael reaction to the formation of disulfides. The majority of the methods used in the synthesis of polymeric drug delivery systems with an incorporated cholesterol molecule are controlled radical polymerizations such as ATRP [54,79,[102][103][104][105][106][107][108], RAFT [91] or NMP [100] (Table 1). This is due to the possibility of controlling the dispersion of the system, which translates into stability in biological properties and accuracy in predicting the behavior of the carrier in the human body.…”
Section: Cholesterol Introduced To the Main Chain During Polymerizationmentioning
confidence: 99%